Regulation of Glucose 6-Phosphate Dehydrogenase in Blue-Green Algae - Grossman, Arthur (1975)
Glucose 6-phosphate dehydrogenase (EC 1.1.1.49) has been partially purified from Anacystis nidulans and Anabaena flos-aquae by means of ammonium sulfate fractionation and exclusion gel chromatography and the kinetic properties determined. Glucose 6-phosphate dehydrogenase from these blue-green algae exhibits Michaelis-Menten kinetics at pH 6.7. At this pH, Km values of 0.37 mm for glucose 6-phosphate and 10 μm for NADP were determined. At a pH above 7.4, the enzyme exhibits sigmoidal kinetics with respect to glucose 6-phosphate saturation but the saturation curve for NADP remains hyperbolic. ATP is an inhibitor of the enzyme competitively with NADP with a Ki of 2 to 5 mm. NADPH inhibits the enzyme competitively with glucose 6-phosphate. The inhibition curves for NADPH are hyperbolic at pH 6.7 and sigmoidal at pH 8.6. The significance of these in vitro kinetics are discussed relative to in vivo data on the control of glucose 6-phosphate turnover in blue-green algae.